SUPLEMENTASI YOGURT FORTIFIKASI KONSENTRASI BERTINGKAT EKSTRAK ROSELLA UNGU TERHADAP KADAR MALONDIALDEHIDA (MDA) DAN GAMBARAN HISTOLOGI GINJAL MENCIT - Ratna, Novia Kumala Dian Nur; Setianingrum, Ani; Nugroho, Widi; Haskito, Ajeng Erika Prihastuti; Noviatri, Aldila (JURNAL KAJIAN VETERINER, 2022)
Purple roselle has ingredients such as organic acids, anthocyanins, polysaccharides, and flavonoids. The antioxidant content in purple roselle has benefits in preventing cell damage due to free radicals. This study was conducted to discoverthe effect of supplementation yogurt fortified with a graded concentration of purple roselle extract on MDA levels and histology of the kidney organs of mice. Laboratory experimental study using 16 male Balb-C mice divided into four groups. The control (C) group was not given any treatment. The treatment groups 1,2, and 3 (T1, T2, T3) were given fortified purple roselle yogurt with concentrations of 5%, 10%, and 15%, respectively. The treatment was carried out for 14 days with a volume of 0.4 ml/day. Kidney organs were collected for histological analysis. Kidney malondialdehydelevels were assayed using the TBARS test and statistically analyzed with a 95% confidence level by one-way ANOVA analysis. Histology score analyzed using the Kruskal-Wallis test followed by the Mann- Whitney test. This study showedthat at concentrations of 10% and 15%, MDA levels of the mice kidneys reduce significantly compared to the control group. The kidney histology score results show some changes in treatment groups compares to control group. The average score decreasing from different treatment group, and the lowest score was group given yogurt fortified roselle extract 15%. The administration of fortified yogurt with purple roselle extract at a concentration of 15% can reduce MDA levels in the kidneys of mice, and the higher the concentration can reduce kidney damage in mice.